2010
DOI: 10.1002/humu.21311
|View full text |Cite
|
Sign up to set email alerts
|

Molecular spectrum of SLC22A5 (OCTN2) gene mutations detected in 143 subjects evaluated for systemic carnitine deficiency

Abstract: Systemic primary carnitine deficiency (CDSP) is caused by recessive mutations in the SLC22A5 (OCTN2) gene encoding the plasmalemmal carnitine transporter and characterized by hypoketotic hypoglycemia, and skeletal and cardiac myopathy. The entire coding regions of the OCTN2 gene were sequenced in 143 unrelated subjects suspected of having CDSP. In 70 unrelated infants evaluated because of abnormal newborn screening (NBS) results, 48 were found to have at least 1 mutation/unclassified missense variant. Twenty-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 16 publications
1
54
0
3
Order By: Relevance
“…As in other previous studies, no genotype-phenotype relationship was observed. (Garavaglia et al 1991;Lamhonwah et al 2002;Li et al 2010;Longo et al 2006;Stanley et al 1991;Wang et al 2000aWang et al , b, 2001). Even siblings with the same mutation have different ages of onset and different progressions of disease pointing to the presence of clinical heterogeneity (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As in other previous studies, no genotype-phenotype relationship was observed. (Garavaglia et al 1991;Lamhonwah et al 2002;Li et al 2010;Longo et al 2006;Stanley et al 1991;Wang et al 2000aWang et al , b, 2001). Even siblings with the same mutation have different ages of onset and different progressions of disease pointing to the presence of clinical heterogeneity (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This therefore suggests that the wide variability in phenotypic expression in carnitine transporter defect is most likely related to exogenous stressors that exacerbate the carnitine deficiency. These could include decreased intake due to dietary carnitine deficiency (vegetarian diets), drugs that increase the elimination of carnitine (valproic acid, pivalic acid) or inhibitors of carnitine transport (verapamil, pyrilamine, b-lactam antibiotics), and conditions such as fasting or infection, which would increase the demands on carnitine-dependent fatty acid oxidation (Holme et al 1989;Lamhonwah et al 2002;Li et al 2010;Spiekerkoetter et al 2003;Tein et al 1993;Toh et al 2010). Lack of genotype/phenotype correlation could also be influenced by polygenic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a point mutation identified by PCR-based DNA sequencing may appear to be homozygous when the other allele contains a deletion spanning the region containing the mutation. 17 A patient could thus be compound heterozygous for two deleterious mutations (one a point mutation and the other a deletion), consistent with affected status. The chance that a new mutation could have occurred in a patient with a recessive disorder who had already inherited an identical mutation from one of the parents, or that one parent has gonadal mosaicism, is highly unlikely, and not considered as part of our standard evaluation of apparently homozygous mutations.…”
Section: Discussionmentioning
confidence: 92%
“…Poza tym w PUNK w biopsji skóry obserwuje się zmniejszenie transportu karnityny przez fibroblasty (< 10%) [31,36]. U niemowląt, u których w przesiewowych testach stwierdzono obniżony poziom karnityny mutacje w genie SLC22A5 wykrywa się u około 70% przypadków [37].…”
Section: Pierwotny Układowy Niedobór Karnitynunclassified